A sensitive and accurate method to simultaneously measure uric acid and creatinine in human saliva by using LC–MS/MS. (December 2017) - Liu, Xin-Ying; Luo, Ying; Zhou, Chun-Yu; Peng, Ai; Liu, Jun-Yan
Aim: To establish a method to simultaneously measure uric acid (UA) and creatinine (Cr) in human saliva.Materials & methods: By using HPLC–MS/MS, we developed and validated a fast, sensitive and accurate method to simultaneously determine UA and Cr in human saliva. The determination range for Cr and UA is of 10–5000 ng/ml with the R 2 for both calibration curves over 0.999. The accuracy, precision and recovery of Cr and UA were all acceptable. By using the established method, the Cr and UA levels in saliva from 28 healthy volunteers were measured as 2.9 ± 0.8 µM and 46.8 ± 18.2 µM, respectively.Conclusion: This method can simultaneously determine Cr and UA in saliva for clinical and translational study.